Time series models show comparable projection performance with joinpoint regression: A comparison using historical cancer data from World Health Organization - Li, Jinhui; Chan, Nicholas B.; Xue, Jiashu; Tsoi, Kelvin K. F. (Frontiers in Public Health, 2022)
Background: Cancer is one of the major causes of death and the projection of cancer incidences is essential for future healthcare resources planning. Joinpoint regression and average annual percentage change (AAPC) are common approaches for cancer projection, while time series models, traditional ways of trend analysis in statistics, were considered less popular. This study aims to compare these projection methods on seven types of cancers in 31 geographical jurisdictions. Methods: Using data from 66 cancer registries in the World Health Organization, projection models by joinpoint regression, AAPC, and autoregressive integrated moving average with exogenous variables (ARIMAX) were constructed based on twenty years of cancer incidences. The rest of the data upon twenty-years of record were used to validate the primary outcomes, namely, three-year, five-year and ten-year projections. Weighted averages of mean-square-errors and of percentage errors on predictions were used to quantify the accuracy of the projection results. Results: Among 66 jurisdictions and seven selected cancers, ARIMAX gave the best five-year and ten-year projections for most of the scenarios. When the ten-year projection was concerned, ARIMAX resulted in a mean-square-error (or percentage error) of 2.7% (or 7.2%), compared with 3.3% (or 15.2%) by joinpoint regression and 7.8% (or 15.0%) by AAPC. All the three methods were unable to give reasonable projections for prostate cancer incidence in the US. Conclusion: ARIMAX outperformed the joinpoint regression and AAPC approaches by showing promising accuracy and robustness in projecting cancer incidence rates. In the future, developments in projection models and better applications could promise to improve our ability to understand the trend of disease development, design the intervention strategies, and build proactive public health system.